Sistematización de una aproximación a la formación docente de primera infancia en contexto de aprendiendo en casa 2020-II, con el proyecto "Aprendiendo de la mano de los niños" (2021)
This systematization aims to leave a written memory of the creation and process of the project "Learning from the hand of children" that resulted in a talent show held during Pedagogical Practice III 2020- -II. It is important to highlight that the project was developed through virtuality due to the health emergency caused by COVID-19 that is happening worldwide, for this reason it led its participants to generate new experiences and learnings in a different way more rigorously, the systematization is carried out with the phases proposed by Oscar Jara, thus allowing to bring an order